THE USE OF ELICITATION IN IMPROVING STUDENTSâ€™ SPEAKING SKILL - Yuli Fitria; Eva Devi Sofyawati (Institut Pendidikan Indonesia Garut, 2018)
This research was entitled â€œThe Use of Elicitation Technique in Improving Studentsâ€™ Speaking Skillâ€. Since there were many students who have problems in learning speaking because the students do not have enough opportunity to speak in English, so they feel uncomfortable to speak and feel awkward to say everything in English because lack of practice. The use of Elicitation technique was choosen as a means to improve an active situation in their speaking skill. This research aimed to found out whether there was any significant effect of using Elicitation as teaching method toward improving studentsâ€™ speaking skill in a junior high school 4 Garut academic year 2015/2016. The participants of the research were consisted of 32 students of second grade. This is a quantitative research using pre-experimental research design. To achieved the purpose, a test including pre-test and post- test was employed. The test was in the form of speaking test which was retelling the story that had been heard. Normalized Gain Test was used to found out the significant difference between studentsâ€™ scores in pre-test and post-test. The data from pre-test and post-test showed that the average of the studentsâ€™ achievement in pre-test was 11.19 and the average of studentsâ€™ achievement in post-test was 56.19 and the result from Normalized Gain showed that 99.9% students can improve their speaking through the use of Elicitation technique. To analyze the data, the t-test was used and it was revealed that the value of tobserved=8.0494 and the value of tcritical=2.0317. The finding showed that tobserved was bigger than tcritical (8.0494 > 2.0317). The tobserved lied in the rejection area of Null Hypothesis (H0). On the contrary, Alternative Hypothesis (Ha) was accepted. Based on the result of study, it can be concluded that Elicitation technique have significant effect in improving studentsâ€™ speaking skill and the use of Elicitation technique made students easier in presenting their ideas. Therefore, the teacher should have the best teaching method to use in teaching and learning process that make students actively speak up in the class and the students should practice their speaking continuously. This result indicates that the use of Elicitation technique is effective to improve studentsâ€™ speaking skill.